2012
DOI: 10.5606/tgkdc.dergisi.2012.101
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative problems experienced by patients undergoing coronary artery bypass graft surgery and their self-care ability after discharge

Abstract: Postoperative problems experienced by patients undergoing coronary artery bypass graft surgery and their self-care ability after dischargeKoroner arter baypas greft cerrahisi yapılan hastaların taburcu edildikten sonra yaşadıkları sorunlar ve öz bakım yetileri Background:In this research, we aimed to assess the postoperative problems experienced by patients who underwent coronary artery bypass graft (CABG) surgery and their self-care ability after discharge.Methods: A total of 53 patients who underwent CABG s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 10 publications
2
31
0
1
Order By: Relevance
“…More than 30% of the patients had self-care abilities, as indicated in previous reports (6). The sample size was calculated using the following formula (Equation 1):…”
Section: Methodssupporting
confidence: 77%
See 2 more Smart Citations
“…More than 30% of the patients had self-care abilities, as indicated in previous reports (6). The sample size was calculated using the following formula (Equation 1):…”
Section: Methodssupporting
confidence: 77%
“…Even though CABG has improved in terms of its success rate, patients still have to deal with a number of physical, psychological, and social problems in the period following discharge from hospital (5). The side effects reported by patients after CABG include a variety of problems such as postoperative pain, insomnia, changes in appetite or taste, chest pain, respiratory difficulties, arrhythmia, palpitations, numbness of the arms, abdominal distention, weight loss, anxiety related to the treatment and their ability to adhere to the recommended physical activity schedule, weakness, headache, vertigo, depression, nausea, and vomiting (6). Patients undergoing cardiac surgery must be well-informed of the potential problems, activity enhancements, nutrition, and medication beforehand since the success of the surgery is highly dependent on the patients’ understanding of the disease and the required activities, including the diet and medical regimen, required after surgery (7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have found that chest and leg pain, edema in the leg incision, numbness in the arms, dyspnea, arrhythmia, constipation, nausea, vomiting, loss of appetite, weight loss, sleep disorders, fatigue, weakness, dizziness, anxiety, and depression are common complications that occur after CABG surgery, and these cause difficulty in activities of daily living (ADLs) in older adults by restricting their functional independence. [1,2,[7][8][9][10][11][12] Comprehensive nursing care, discharge training, and counseling after discharge are crucial components which can decrease the postoperative problems of older adults and increase their functional independence. Discharge training and counseling can also decrease the length of hospital stays, reduce the number of postoperative complications, lower healthcare expenses, limit the chances for rehospitalization/ admission after discharge, and increase functional independence levels and the patients' quality of life (QoL).…”
mentioning
confidence: 99%
“…Despite great advances in treatment of cardiovascular diseases, patients are still experiencing several physical, mental and social problems after surgery (9). Overall, 7461 cases of heart valve replacement procedures were performed in Brazil in 2012 with 8% mortality rate; this is while mortality rate was 4.6% in most of the analysis of other studies (10).…”
Section: Introductionmentioning
confidence: 99%